Review of Forensic Medicine and Toxicology - Biswas Gautam; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2012)
Review of Forensic Medicine and Toxicology is presented in a concise and lucid form with line-diagrams, boxes, tables, differentiations and flow charts designed to make the book interesting-to-read, easy-to-comprehend, recollect and reproduce. All topics are updated and recent advances/changes have been incorporated wherever needed. Section two (Toxicology) has been updated and some additional matter has been added. Hence, like in the previous edition, topic-wise MCQs from the last 10 years are given at the end of the chapters. Answers can be referred in the text which is given as superscripts. This will not only make the subject interesting, but also help the reader to get insight of that topic and prepare for viva-voce. Question bank I and II (Q-Bank) give a list of important questions, which the students should prepare for the professional examination and are based on the latest MBBS curriculum prepared by Directorate General of Health Services and Medical Council of India (MCI). There are two separate categories$1 (Bmust know and desirable to know, the student may prepare according to the time and can devote to the subject. This edition of the book will find favorable response from medical students as earlier and also offer significant help to medical practitioners, in-service doctors and forensic scientists.s
Keywords: Forensic Medicine,MCQs and Self-assessment; Electronic books